Reparação do diafragma de cães com segmento intestinal livre homógeno conservado em solução hipersaturada de açúcar - Mota, Francisco Cláudio Dantas (2002)
Surgical repair using biological or sinthetic implants is indicated in diaphragmatic defects, congenital or traumatic, that prevent the approximation of the wound borders. The aim of this study was to evaluate the clinic, macroscopic and histologic features of the tissue integration of homologous intestinal segment free of epithelium and lamina própria of the mucous túnica preserved in supersaturated sugar solution in the repair of defects (7.0 x 4.0 cm) in the diaphragm muscle of 16 dogs, through accession via paracostal. The diaphragmatic defect was closed with the intestinal segment by separated simple points using polyglactin 910 3-0 wire. The animais were divided into four groups containing 4 dogs per group, and submitted to new surgery at 15, 30, 50 and 90 days, representing the experimental groups I, II, III and IV, respectively, for macroscopic and histopathologic assays. All animais showed a good clinicai evolution. Macroscopically, adherences were observed between the implanted area and organs, such as liver and parietal pleura. Only one animal showed adherence with the lung. By histologic assays, the graft induced a minor inflammatory reaction with replacement by dense connective tissue. The homologous intestinal segment free of epithelium and lamina própria of the mucous túnica preserved in supersaturated sugar solution supported the expansion movements of the diaphragm and was replaced by a thin layer of fíbrous connective tissue.